SISTEM INFORMASI HOTEL KING SAROLANGUN: Reservations, Information Systems, Waterfall, DFD - Taufiqurahman, Ahmad; -, Afrizal (JURNAL AKADEMIKA, 2019)
The technological development is still very specific in the field of information. This is caused by the increasing human need for fast and accurate information. With the development of the technology expected to be able to help the employees, the only one is the hotel business. In the world hotels can be categorized as preserving the rooms of consumers. During this time the King Sarol Hotel built a telephone reservation, fax or consumer arrived at the hotel. Data recording is done by a manual employee. In this study I want to build a Reserve Information System based on Web using the Waterfall method and the DFD as the design method for facilitating the client's resources in preserving, and facilitating staff in recording and processing data as well as making reports and publishing more extensive King Sarolangundenganskala Hotels. The system is built using the PHP phases of the MySQL database and Web Server as its web server.